From Neoliberal Openness to Sovereign Openness: Analysing Imaginaries of European Digital Policies - Münßinger, Max; Schröder-Bergen, Susanne; Glasze, Georg (Geopolitics, 2025)
Numerous studies have shown that the adoption of ‘digital sovereignty’ as a guiding principle in European digital policy has marked a discursive break. While EU digital policies until the 2000s were shaped by ideas of a dismantling of borders and an opening up into a global information society, ‘sovereignty’ connotes delimitation and autonomy. Yet several recent European digital policies link ‘digital sovereignty’ also to ‘openness’. To explain this paradoxical observation, this paper adopts a cultural political economy perspective. We begin by reconstructing how the established imaginary of ‘digital openness’ has been confronted and rearticulated by demands for ‘digital sovereignty’ and then focus on two current arenas of European digital policy: the creation of a European ‘open’ cloud, and the promotion of ‘open’ digital commons. We show that ‘openness’ remains a key concept in EU digital policy, but ‘market-opening’ forms of openness have been replaced by a ‘market-protecting’ ‘sovereign openness
CRIS-Team Scopus Importer:2025-05-30